Wave–particle resonance condition test for ion-kinetic waves in the solar wind - Y. Narita; Y. Narita; E. Marsch; C. Perschke; C. Perschke; K.-H. Glassmeier; K.-H. Glassmeier; U. Motschmann; U. Motschmann; H. Comişel; H. Comişel (Annales Geophysicae, 2016)
Conditions for the Landau and cyclotron resonances are tested for 543 waves (identified as local peaks in the energy spectra) in the magnetic field fluctuations of the solar wind measured by the Cluster spacecraft on a tetrahedral scale of 100 km. The resonance parameters are evaluated using the frequencies in the plasma rest frame, the parallel components of the wavevectors, the ion cyclotron frequency, and the ion thermal speed. The observed waves show a character of the sideband waves associated with the ion Bernstein mode, and are in a weak agreement with the fundamental electron cyclotron resonance in spite of the ion-kinetic scales. The electron cyclotron resonance is likely taking place in solar wind turbulence near 1 AU (astronomical unit).